Recovery of uranium from phosphate ore in the Sheikh Habil-Iran mine: part I— multivariable optimization of leaching process using the response surface method - Abdeshahi, A.; Outokesh, M.; Nejad, D. Ghoddocy; Zare, M. Habibi; Sadeghi, M. H. (Frontiers in Chemistry, 2023)
In this research, the recovery of uranium from the phosphate ore of Sheikh Habil-Iran mine using flotation/calcination-leaching processes has been investigated. The 75-150 μm phosphate ore particles size, sodium oleate as a collector with a concentration of 2000 g/ton of rock, pH=10, 5 min flotation time were obtained as optimum parameters of flotation by reverse method led to phosphate ore with a grade of 180 ppm UO2, 36.1% P₂O₅, 7.22% SiO2 and CaO/P₂O₅ =1.23. The optimum calcination parameters were selected as 100 μm phosphate ore particles size at D80, 900°C temperature, and 2 h heating time, which resulted in phosphate ore with a grade of 173 ppm UO2 and 31.9% P₂O₅. The L/S (liquid to solid ratio) =5, 3 M sulfuric acid concentration, 80°C temperature, and 5 h leaching time were obtained as optimum leaching parameters by response surface methodological approach. The efficiency of uranium recovery from phosphate ore pretreated by flotation and calcination methods were 84.2 % and 75.2%, respectively. The results indicated that the flotation has superiority over calcination as a pre-treatment method of phosphate ore of Sheikh Habil-Iran mine.